2014
DOI: 10.1152/japplphysiol.00151.2014
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training reduces arterial stiffness in metabolic syndrome

Abstract: The metabolic syndrome (MetS) is associated with a threefold increase risk of cardiovascular disease (CVD) mortality partly due to increased arterial stiffening. We compared the effects of aerobic exercise training on arterial stiffening/mechanics in MetS subjects without overt CVD or type 2 diabetes. MetS and healthy control (Con) subjects underwent 8 wk of exercise training (ExT; 11 MetS and 11 Con) or remained inactive (11 MetS and 10 Con). The following measures were performed pre- and postintervention: ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 42 publications
7
83
3
4
Order By: Relevance
“…There were no main exercise effects in left brachial MAP following exercise, however the exercise*∆MAP interaction effect in ∆MAP adjusted analysis showed that those participants with small ∆MAP decreased lower limb PWV more following exercise, suggesting that the mechanisms responsible for the alteration in PWV may be related at least in part to the hemodynamic response (Donley et al 2014). Other studies found reductions in stiffness after acute aerobic exercise (Heffernan et al 2007a;Kingwell et al 1997), and increases in stiffness after acute resistance exercise (DeVan et al 2005), with no change in brachial mean blood pressure.…”
Section: Page 21 Of 40mentioning
confidence: 82%
“…There were no main exercise effects in left brachial MAP following exercise, however the exercise*∆MAP interaction effect in ∆MAP adjusted analysis showed that those participants with small ∆MAP decreased lower limb PWV more following exercise, suggesting that the mechanisms responsible for the alteration in PWV may be related at least in part to the hemodynamic response (Donley et al 2014). Other studies found reductions in stiffness after acute aerobic exercise (Heffernan et al 2007a;Kingwell et al 1997), and increases in stiffness after acute resistance exercise (DeVan et al 2005), with no change in brachial mean blood pressure.…”
Section: Page 21 Of 40mentioning
confidence: 82%
“…The assessment of arterial stiffness using Sphygmocor before and after 8 weeks of heart rate controlled physical training in 22 MetS patients was performed by Donley et al [9]. The improvement of aortic and peripheral arterial stiffness parameters after exercising was shown in this study.…”
Section: Discussionmentioning
confidence: 51%
“…Various modalities of physical training -aerobic, aerobic interval, strength -are used in MetS subjects [10,23,24]. Since previous studies usually implemented 8 or more week duration training programmes in these subjects [9][10][11]25], we assessed if short 4-week duration supervised aerobic physical training could have some initial impact on anthropometric, metabolic, hemodynamic and arterial wall parameters in MetS subjects. We have demonstrated that short-duration supervised aerobic physical training improves anthropometric parameters, metabolic profile, and arterial wall parameters, and could serve as the initial step for continuous improvement of physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…skeletal muscle perfusion; vascular remodeling; vascular reactivity; rodent models of obesity; nitric oxide bioavailability; chronic inflammation EPIDEMIOLOGICAL STUDIES HAVE clearly and consistently demonstrated that both the incidence and prevalence of the metabolic syndrome is continuing to increase in Western society and in most developed economies worldwide (4, 9, 24). Although each of the constituent systemic pathologies (e.g., impaired glycemic control, atherogenic dyslipidemia, hypertension, obesity) have been well documented to increase the risk for development of impaired vascular structure/function and peripheral vascular disease (PVD) (10,11,13,14,16,25,29,45), the significance of this multi-pathology state is that it increases the risk for individuals to develop PVD well beyond that for any single contributing element. Given the impact of PVD on life expectancy, quality of life, depression, and the direct (health care) and indirect (lost productivity) economic costs to society (3, 41, 44), considerable emphasis has been placed on not only the study of PVD and its contributing elements in human subjects but also for the detailed investigation of appropriate animal models of vasculopathy in the metabolic syndrome (1, 49, 51).…”
mentioning
confidence: 99%